AeU's 4th Convocation Ceremony and graduates achievements. - New, Sabah Times (New Sabah Times, 2014)
4th Convocation Ceremony at Putra World Trade Centre (PWTC) - 1200 students received their scrolls - Hadi Satria Putra graduated in BICT (hons) with a specialization in Information System at AeU